Impacts of Nitrate and Nitrite on Physiology of Shewanella oneidensis - Zhang, Haiyan (Public Library of Science, 2013)

(untitled)
Shewanella oneidensis exhibits a remarkable versatility in anaerobic respiration, which largely relies on its diverse respiratory pathways. Some of these are expressed in response to the existence of their corresponding electron acceptors (EAs) under aerobic conditions. However, little is known about respiration and the impact of non-oxygen EAs on the physiology of the microorganism when oxygen is present. Here we undertook a study to elucidate the basis for nitrate and nitrite inhibition of growth under aerobic conditions. We discovered that nitrate in the form of NaNO(3) exerts its inhibitory effects as a precursor to nitrite at low concentrations and as an osmotic-stress provider (Na(+)) at high concentrations. In contrast, nitrite is extremely toxic, with 25 mM abolishing growth completely. We subsequently found that oxygen represses utilization of all EAs but nitrate. To order to utilize EAs with less positive redox potential, such as nitrite and fumarate, S. oneidensis must enter the stationary phase, when oxygen respiration becomes unfavorable. In addition, we demonstrated that during aerobic respiration the cytochrome bd oxidase confers S. oneidensis resistance to nitrite, which likely functions via nitric oxide (NO).